Study of humidity and water activity of cork slabs during cork stopper manufacturing process: preliminary results - Pires,J. M. C. (2007)
The main goal of this work was to make evidence of the applicability in the cork stopper industry of a control method along the cork slabs maturing stage after boiling, aiming to ensure the adequate conditions for Chrysonilia sitophila colonisation of cork slabs during that period, avoiding the development of other fungi. Cork humidity and water activity (wa) were used as indicators. Comparing the drying rate of the outer and the inner parts of the bark it could be observed, under the assay conditions, that to attain 0.9 wa, (the critical point for C. sitophila development), 39.8h were necessary in the case of outer bark while inner bark only need 20.4h. As the visible part of the cork slabs corresponds more to its outer part, the time of 40h can be taken as a good visible indicator to limit the cork slabs maturing period after boiling. Moreover it could be observed that under that period of time the evident prevailing fungus on the cork slabs was C. sitophila so probably assuring low probabilities of cork taint occurrence, under the conditions propose on this study.